Discussion: Atterberg limits determination and soil classification using fall cone device on the silty sands and sandy silts [International Journal of Geotechnical Engineering 19(1-3): 78-87] - O'Kelly, Brendan (My University, 2025)
This article presents a discussion of the original research reported in the paper by Marušić and Jagodnik (the Authors) that was published in the International Journal of Geotechnical Engineering 19(1–3): 78–87. The Authors employed the fall-cone (FC) method, along with examining two existing FC-based proposals, for determining the Atterberg consistency limits of various sand– kaolinite (SK) mixtures, with sand contents of 0–90% (dry mass basis). Additionally, they investi- gated the classification of these SK mixtures using the conventional Casagrande plasticity chart and the recently developed FC-based Vardanega et al. plasticity chart. As described in this discussion article, several shortcomings have been identified in the Authors’ investigation, includ- ing their misassignment of plasticity credentials for some of their investigated SK mixtures, which led to incorrect soil classifications under both the Casagrande and Vardanega et al. classification methodologies. In other words, it is an implicit and integral first step that, before employing these FC-based proposals, the plasticity credentials of the investigated soils must be verified experimentally.
PUBLISHED
Keywords: Atterberg limits; fall cone; soil plasticity; soil classification; sand–kaolinite; Smart & Sustainable Planet; Atterberg limits; Fall cone; GEOTECHNICAL ENGINEERING; Geotechnics; Soil Mechanics; Soil Mechanics & Foundations; cone penetrometer; consistency limits; geotechnical; soil classification; soil plasticity